Asymmetric cell division of ALDH1-positive cancer stem cells generates glycolytic metabolically diverse cell populations - Shoma Tamori; Chika Matsuda; Takahiro Kasai; Shigeo Ohno; Kazunori Sasaki; Kazunori Akimoto (Scientific Reports)
Abstract Metabolic heterogeneity in various cancer cells within a tumor causes resistance to medical therapies and promotes tumor recurrence and metastasis. However, the mechanisms by which tumors acquire metabolic heterogeneity are poorly understood. Here, we revealed that PKCλ-dependent asymmetric division of ALDH1-positive cancer stem cells (CSCs) led to an uneven distribution of glycolytic capacity, which is crucial for understanding metabolic heterogeneity within a tumor. The rate-limiting enzyme PFKP and the metabolic probe CDG in glycolysis codistributed with the ALDH1A3 protein during the post-cell division phase, highlighting a mechanism for acquiring metabolic diversity. PKCλ deficiency reduced the asymmetric distribution of these proteins in ALDH1high cells with high ALDH1 activity, suggesting a fundamental role for PKCλ in metabolic heterogeneity. We identified 28 distinct distribution patterns combining PFKP and CDG distributions, demonstrating the complexity of glycolytic heterogeneity. Furthermore, validation and prediction of cell distribution patterns via a probabilistic model confirmed that PKCλ deficiency diminished glycolytic diversity in individual cells within a cancer cell colony generated from an ALDH1-positive CSC. These findings suggest that PKCλ-dependent asymmetric cell division of ALDH1-positive CSCs is crucial for glycolytic heterogeneity in cancer cells within a tumor, potentially offering new therapeutic targets against tumor resistance and metastasis.